Skin wound healing part I: ancestral and modern medicines for the development of new technologies - Rodriguez, Andrea Paola; Romero, Amanda Guadalupe; Kozuszko, Silvia Noemi; Comotti, Lucca; Nagano, Kenichi; Felice, Carmelo José; Katase, Naoki (Frontiers in Soft Matter, 2025)
The human body, once regarded primarily as a spiritual vessel, is now understood as a highly complex biological system governed by intricate cellular and molecular processes. As civilizations and technologies have evolved, so too have the methodologies, materials, and epistemologies surrounding wound care. From herbal applications in ancient cultures to the development of bioengineered dressings in contemporary medicine, the field of wound healing reflects a continuous trajectory of innovation and adaptation. This review presents a concise overview of wound management practices across diverse cultural contexts, highlighting the contributions of ancestral knowledge systems. It further examines the current landscape of wound dressing technologies, with particular emphasis on soft materials engineered, such as polymers, gels, and foams, to optimize healing outcomes in both acute and chronic wounds. In seeking deeper integration of ancestral knowledge into biomedical innovation, this review explores clinical trials, patent activity, regulatory standards, and epistemological considerations related to medicinal plant applications. By honoring origin and embracing plural knowledge systems, we aim to advance the development of wound care nanotechnologies that are not only scientifically robust but also culturally inclusive, ethically grounded, and accessible across diverse healthcare settings. The second part of this review summarizes tissue engineering in the market and clinical trials, plant-based remedies and pharmacopoeias, medicinal activities of the plants, analyzing skin wound healing from traditional cataplasm to advanced wound dressings within a holistic framework.